KIF2C affects sperm cell differentiation in patients with Klinefelter syndrome, as revealed by RNA‐Seq and scRNA‐Seq data. Issue 8 (16th June 2022) - He, Haihong; Huang, Tingting; Yu, Fan; Chen, Keyan; Guo, Shixing; Zhang, Lijun; Tang, Xi; Yuan, Xinhua; Liu, Jiao; Zhou, Yiwen
Abstract : Klinefelter syndrome (KS) is a leading contributor to male infertility and is characterised by complex and diverse clinical features; however, genetic changes in the KS transcriptome remain largely unknown. We therefore used transcriptomic and single‐cell RNA sequencing (scRNA‐seq) datasets from KS versus normal populations through the Gene Expression Omnibus (GEO) database to identify gene biomarkers associated with the occurrence of KS. We identified a total of 700 differentially expressed genes (DEGs) and completed Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), enrichment pathway analysis and protein‐protein interaction (PPI) network analysis. A total of four unreported KS‐related hub genes ( KIF2C, MRPS2, RPS15 and TSFM ) were identified. Validation of the single‐cell sequencing dataset showed that only KIF2C and RPS15 were expressed in spermatocytes and that they were differentially expressed in sperm cells. Further construction of the developmental trajectories of these two genes in sperm cells showed that the KIF2C gene showed an upward trend throughout the differentiation and development of sperm cells. In conclusion, we report here that KIF2C may be closely related to the differentiation and development of sperm cells in KS patients, which is important for revealing the molecular mechanism of KS and conducting further studies. Abstract : Klinefelter syndrome (KS) is a genetic cause of male infertility. We used DEGs, constructed PPI networks, screened for Hub genes and validated them with scRNA‐seq data to identify KIF2C as most associated with sperm development. This finding may lead to new options for the treatment of KS patients.